2013
DOI: 10.1007/s00134-013-2977-x
|View full text |Cite
|
Sign up to set email alerts
|

The ETHICA study (part II): simulation study of determinants and variability of ICU physician decisions in patients aged 80 or over

Abstract: Physician decisions for elderly patients had low agreement and varied greatly with bed availability and knowledge of patient preferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 33 publications
0
56
0
1
Order By: Relevance
“…Given limitations in ICU bed availability, this poses challenges to the ICU triage decision-making process. Indeed, old age as such is for some physicians a reason for refusing ICU admission [3]. The ethical dilemma lies on the will to not admit old patients because they are believed to have a poor prognosis or perceived poor quality of life, thereby possibly refusing to admit those old patients for whom ICU care can make a difference.…”
mentioning
confidence: 99%
“…Given limitations in ICU bed availability, this poses challenges to the ICU triage decision-making process. Indeed, old age as such is for some physicians a reason for refusing ICU admission [3]. The ethical dilemma lies on the will to not admit old patients because they are believed to have a poor prognosis or perceived poor quality of life, thereby possibly refusing to admit those old patients for whom ICU care can make a difference.…”
mentioning
confidence: 99%
“…A panel of 4 intensivists was asked the same questions for the different case-scenarios. The results highlighted a great heterogeneity among the physicians and much more aggressive treatments suggested than what patients' wished [23]. However, after receiving information about the patient's choices, physicians' decision to administer ICU treatment decreased…”
Section: Impact Of Age On Decisionsmentioning
confidence: 95%
“…dramatically [23]. This emphasizes the need to communicate with the patient and his/her family whenever possible.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Demographic factors associated with higher refusal rates of some treatment included being married and female sex; however, lower quality of life was associated with higher refusal rates of all treatments. In the second part of this study, Garrouste-Orgeas and colleagues reported the results of a simulation study examining physician decisions regarding the care of patients aged over 80 [60]. The simulation involved decisions about NIV, IMV, and RRT-IMV and included variation in bed availability and patient preferences.…”
Section: ''Ethics and Legal'' Sectionmentioning
confidence: 99%